Key influences on the decision to initiate PrEP among adolescent girls and young women within routine maternal child health and family planning clinics in Western Kenya. Issue 3 (4th March 2022) - Rogers, Zoe; Pintye, Jillian; Kinuthia, John; O'Malley, Gabrielle; Abuna, Felix; Escudero, Jaclyn; Mugambi, Melissa; Awuor, Mercy; Dollah, Annabell; Dettinger, Julia C.; Kohler, Pamela; John-Stewart, Grace; et al.
ABSTRACT: We sought to understand influences on PrEP uptake among Kenyan adolescent girls and young women (AGYW) whose decision on PrEP use was misaligned with their risk for HIV acquisition. In-depth interviews were conducted with 47 Kenyan HIV-negative AGYW aged 15–24 years who were offered PrEP during routine maternal and child health and family planning services. AGYW were sampled from two groups (1) declined PrEP and had ≥1 sexual partner(s) of unknown HIV status and (2) initiated PrEP and reported having one HIV-negative partner. AGYW with HIV-negative partners initiated PrEP due to known or suspected infidelity. AGYW with partners of unknown HIV status recognized PrEP as a helpful HIV prevention tool, yet worried about partner reactions and prioritized avoiding uncomfortable or unsafe situations over PrEP. Among pregnant AGYW, the responsibility of motherhood and providing a future for one's family, through staying healthy and remaining HIV-free, was a strong PrEP use motivator. Among AGYW who desired future motherhood, fears that PrEP could negatively impact fertility or reduce contraceptive effectiveness led to declining PrEP. Peers positively influenced PrEP decision-making, especially personally knowing a PrEP user. Strategies are needed to enhance messaging and delivery approaches that are tailored to AGYW, including peer-led strategies.